Epidemiology of endometriosis: a large population‐based database study from a healthcare provider with 2 million members. (14th June 2017) - Eisenberg, VH; Weil, C; Chodick, G; Shalev, V
Abstract : Objective: Endometriosis constitutes a significant burden on the quality of life of women, their families and healthcare systems. The objective of this study is to describe the real‐world epidemiology of endometriosis in an unselected low‐risk population in Israel. Design: Retrospective population‐based study. Setting and sample: The computerised databases of Maccabi Healthcare Services (MHS), a 2‐million‐member healthcare provider representing a quarter of the Israeli population. Methods: The crude point prevalence (31 December 2015; diagnosed since 1998) and annual incidence (2000–2015) rates of diagnosed endometriosis (ICD‐9‐CM 617.xx) were assessed among women aged 15–55 years. Prevalent patients were characterised in terms of sociodemographic and clinical characteristics, including validated MHS infertility and chronic disease registries. Main outcome measures: Prevalence and incidence of diagnosed endometriosis in MHS. Results: The point prevalence of endometriosis [ n = 6146, mean age 40.4 ± 8.0 years (SD)] was 10.8 per 1000 (95% CI 10.5–11.0). Women aged 40–44 years had the highest prevalence rate of 18.6 per 1000 (95% CI 17.7–19.5). Infertility was documented in 37% of patients. A total of 6045 patients were included in the cohort of newly‐diagnosed endometriosis (mean age 34.0 ± 8.1 years), corresponding to an average annual incidence rate of 7.2 per 10 000 (95% CI 6.5–8.0). Conclusions: We observed a substantially lower prevalence of diagnosed endometriosis compared with previous reports in high‐risk populations, in line with population‐based estimates from European databases (range 0.8–1.8%). Further characterisation of this cohort may help to understand what affects the prevalence of endometriosis in Israel, and to promote earlier diagnosis and improve management in clinical practice. Tweetable abstract: Endometriosis diagnosed in 1% of women, according to a large population‐based study in a community setting. Tweetable abstract: Endometriosis diagnosed in 1% of women, according to a large population‐based study in a community setting.